A 'Primus Inter Pares' in EU Foreign Policy? – German Leadership in the European Council during the Libyan and Ukrainian Crises. Issue 1 (2nd January 2020) - von Weitershausen, Inez; Schäfer, David; Wessels, Wolfgang
Abstract : Drawing on the characterisation of the European Council as an arena for 'integrative bargaining', the paper shows the importance of two factors that influence whether a country can act as 'first among equals' or ('Primus Inter Pares') in a system designed to respect national sovereignty: alignment among the 'Big Three', and 'voice opportunities' for smaller member states. We support this argument with view of Germany's divergent role in two recent international crises - the 2011 uprisings in Libya and the violent protests in Ukraine in 2014/2015. On the basis of these findings, we conclude that the ability to create consent among all Member States is both a key prerequisite and a serious challenge for effective leadership in EU foreign policy.